PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PENGGUNA MOBILE BANKING - Elin Nur Kuatin; Imronudin Imronudin (LP2M Universitas Bina Bangsa, 2024)
This study aims to test the quality of service on the loyalty of mobile banking users. This type of research is quantitative. The source of data used in this study is primary data. The population of this study is bank customers who use mobile banking. The sampling technique in this study used Purposive Sampling. The sample size of this study was 150 respondents. The data collection technique used in this study was a survey through questionnaires. The data analysis technique of this research is to use the Structural Equation Model (SEM) with Partial Least Square (PLS). Quality of Service consisting of Reliability, User-Friendliness, Security and Efficiency. has a significant effect on loyalty. This explains that the better the quality of service in mobile banking, the higher the loyalty of mobile banking users. User loyalty is a conative component where users will have the intention to use mobile banking in the long run. Because you have confidence in the use of a service